The Parenting Experience of Those With Borderline Personality Disorder Traits: Practitioner and Parent Perspectives - Dunn, Abigail; Cartwright-Hatton, Sam; Startup, Helen; Papamichail, Alexandra (Frontiers in Psychology, 2020)
Background: Borderline Personality Disorder (BPD) is associated with challenges around emotional intensity and interpersonal difficulties. The children of parents with BPD are at risk of poorer outcomes in terms of their own mental health, educational outcomes and wellbeing. The challenges of being a parent can also exacerbate the symptoms of those with BPD traits. There is a pressing need to understand the experience of these parents and to determine what support would be appropriate and useful. Aim: To explore and compare the experiences and support needs of parents with BPD traits with the experiences and understanding of practitioners who work with them. Methods: Interviews with 12 parents with BPD traits and 21 practitioners with experience of working with individuals with BPD. The two strands of interviews were analysed independently using a thematic framework approach, after which the superordinate and subordinate themes were subject to comparison. Results: Parents with BPD traits represent themselves as experiencing considerable challenges in their role as a parent. These included the impact of emotional intensity, social isolation and lack of a positive parenting models to draw upon. Practitioners demonstrated a strong degree of shared understanding into these difficulties. Both groups highlighted a lack of appropriate support for these parents. Conclusion: This research highlights the clinical need for parenting-focused support for individuals with BPD traits. Preliminary suggestions for format and content are given.